Influence of mannan oligosaccharide supplementation on haematological and immunological responses and disease resistance of striped catfish (Pangasianodon hypophthalmus Sauvage, 1878) juveniles - Akter, N; Hashim, R; Sutriana, A; Nor, SAM (Springer, 2024)
Indexed by WOS/ Scopus